Broadband Wireless Access in Egypt - World Bank (Washington, DC, 2013)
This paper discusses current and future developments in wireless technology and infastructure in Egypt. One of the important regulatory decisions made in Egypt is that policy related to broadband wireless will be technology neutral. Consequently, the regulator cannot decide about which operators should use specific technologies. This approach is beneficial for the overall development of the market and deployment of networks because: It allows operators and service providers to decide on which technology or mix of technologies is best for given service and market requirements, budget outlays, and deployment scenarios. Such an approach promotes technical and economic efficiency since each service providerwill attempt to maximize revenues and their subscriber base. The flexibility allows the regulator to ensure that the market can deploy the latest technology with the least regulatory overhead. Allowing only one technology into the market place will restrict the range of choices available to consumers.